Future impact of traffic emissions on atmospheric ozone and OH based on two scenarios - Hodnebrog, Ø.; Berntsen, T. K.; Dessens, O.; Gauss, M.; Grewe, V.; Isaksen, I. S. A.; Koffi, B.; Myhre, G.; Olivié, D.; Prather, M. J.; Stordal, F.; Szopa, S.; et al. (Atmospheric Chemistry and Physics, 2012)
The future impact of traffic emissions on atmospheric ozone and OH has been investigated separately for the three sectors AIRcraft, maritime SHIPping and ROAD traffic. To reduce uncertainties we present results from an ensemble of six different atmospheric chemistry models, each simulating the atmospheric chemical composition in a possible high emission scenario (A1B), and with emissions from each transport sector reduced by 5% to estimate sensitivities. Our results are compared with optimistic future emission scenarios (B1 and B1 ACARE), presented in a companion paper, and with the recent past (year 2000). Present-day activity indicates that anthropogenic emissions so far evolve closer to A1B than the B1 scenario. As a response to expected changes in emissions, AIR and SHIP will have increased impacts on atmospheric O3 and OH in the future while the impact of ROAD traffic will decrease substantially as a result of technological improvements. In 2050, maximum aircraft-induced O3 occurs near 80° N in the UTLS region and could reach 9 ppbv in the zonal mean during summer. Emissions from ship traffic have their largest O3 impact in the maritime boundary layer with a maximum of 6 ppbv over the North Atlantic Ocean during summer in 2050. The O3 impact of road traffic emissions in the lower troposphere peaks at 3 ppbv over the Arabian Peninsula, much lower than the impact in 2000. Radiative forcing (RF) calculations show that the net effect of AIR, SHIP and ROAD combined will change from a marginal cooling of −0.44 ± 13 mW m−2 in 2000 to a relatively strong cooling of −32 ± 9.3 (B1) or −32 ± 18 mW m−2 (A1B) in 2050, when taking into account RF due to changes in O3, CH4 and CH4-induced O3. This is caused both by the enhanced negative net RF from SHIP, which will change from −19 ± 5.3 mW m−2 in 2000 to −31 ± 4.8 (B1) or −40 ± 9 mW m−2 (A1B) in 2050, and from reduced O3 warming from ROAD, which is likely to turn from a positive net RF of 12 ± 8.5 mW m−2 in 2000 to a slightly negative net RF of −3.1 ± 2.2 (B1) or −3.1 ± 3.4 (A1B) mW m−2 in the middle of this century. The negative net RF from ROAD is temporary and induced by the strong decline in ROAD emissions prior to 2050, which only affects the methane cooling term due to the longer lifetime of CH4 compared to O3. The O3 RF from AIR in 2050 is strongly dependent on scenario and ranges from 19 ± 6.8 (B1 ACARE) to 61 ± 14 mW m−2 (A1B). There is also a considerable span in the net RF from AIR in 2050, ranging from −0.54 ± 4.6 (B1 ACARE) to 12 ± 11 (A1B) mW m−2 compared to 6.6 ± 2.2 mW m−2 in 2000.